Behavior of a Pentacle Connected Five-Phase IM Supplied by a Rectangular Voltage - Pavel Zaskalicky (Advances in Electrical and Electronic Engineering, 2020)
The presented article deals with the steady-state analysis of five-phase Induction Motor (IM), which is supplied by rectangular voltage from a five-leg Voltage Source Inverter (VSI). The new proposed approach is derived from complex Fourier-series using to express inverter terminal voltages. Based on mathematically described inverter output voltages, a formula for VSI output space phasor was derived. Assuming sinusoidal motor winding distribution and on the basis of motor parameters, stator and rotor current space phasors for defined motor load were determined. Finally, the electromagnetic torque ripple waveforms for different IM operation states were investigated.